2014
DOI: 10.2215/cjn.07720713
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Ceruloplasmin, a Regulator of Nitric Oxide Activity, and Incident Cardiovascular Risk in Patients with CKD

Abstract: Background and objectives Increased serum levels of the acute-phase reactant ceruloplasmin predict adverse clinical outcomes in the setting of acute coronary syndromes and heart failure, but their role in patients with CKD is unclear. This study investigated the relationship of ceruloplasmin with clinical outcomes in CKD, especially with regard to traditional cardiac biomarkers.Design, setting, participants, & measurements Serum ceruloplasmin levels in consecutive study participants with CKD (n=654; estimated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 22 publications
(19 reference statements)
0
15
0
2
Order By: Relevance
“…This observation is in agreement with a study by Samokyszyn et al [39] which suggested that Cp can inhibit XO. According to Kennedy et al [40], Cp can show both pro-oxidant and antioxidant capacity and there might be a homeostatic balance between the two states that prevails under different conditions. As a pro-oxidant, NO oxidase function of Cp may predominate which promotes nitrative stress and disease progression, while as an antioxidant, Cp can remove free ferrous iron and therefore can reduce a major producer of superoxide and hydroxyl radicals.…”
Section: Discussionmentioning
confidence: 99%
“…This observation is in agreement with a study by Samokyszyn et al [39] which suggested that Cp can inhibit XO. According to Kennedy et al [40], Cp can show both pro-oxidant and antioxidant capacity and there might be a homeostatic balance between the two states that prevails under different conditions. As a pro-oxidant, NO oxidase function of Cp may predominate which promotes nitrative stress and disease progression, while as an antioxidant, Cp can remove free ferrous iron and therefore can reduce a major producer of superoxide and hydroxyl radicals.…”
Section: Discussionmentioning
confidence: 99%
“…Increased serum activity has been linked to long-term adverse cardiovascular events. This relationship was strong even after multivariable model adjustment for traditional clinical and biological risk factors [23]. Antihypertensive treatment has been shown to decrease Cp activity [24].…”
Section: Discussionmentioning
confidence: 99%
“…The levels of this protein are increased by proinflammatory agonists of the acute-phase reaction [22]. Elevated serum CP has been associated with increased cardiovascular risk [23] and albuminuria in men with type 2 diabetes mellitus [24].…”
Section: Discussionmentioning
confidence: 99%